Magnetically Encoded Luminescent Composite Nanoparticles through Layer‐by‐Layer Self‐Assembly. Issue 45 (26th September 2014) - Song, Erqun; Han, Weiye; Xu, Hongyan; Jiang, Yunfei; Cheng, Dan; Song, Yang; Swihart, Mark T.
Abstract Sensitive and rapid detection of multiple analytes and the collection of components from complex samples are important in fields ranging from bioassays/chemical assays, clinical diagnosis, to environmental monitoring. A convenient strategy for creating magnetically encoded luminescent CdTe@SiO2@n Fe3O4 composite nanoparticles, by using a layer‐by‐layer self‐assembly approach based on electrostatic interactions, is described. Silica‐coated CdTe quantum dots (CdTe@SiO2) serve as core templates for the deposition of alternating layers of Fe3O4 magnetic nanoparticles and poly(dimethyldiallyl ammonium chloride), to construct CdTe@SiO2@n Fe3O4 (n=1, 2, 3, …︁) composite nanoparticles with a defined number (n) of Fe3O4 layers. Composite nanoparticles were characterized by zeta‐potential analysis, fluorescence spectroscopy, vibrating sample magnetometry, and transmission electron microscopy, which showed that the CdTe@SiO2@n Fe3O4 composite nanoparticles exhibited excellent luminescence properties coupled with well‐defined magnetic responses. To demonstrate the utility of these magnetically encoded nanoparticles for near‐simultaneous detection and separation of multiple components from complex samples, three different fluorescently labeled IgG proteins, as model targets, were identified and collected from a mixture by using the CdTe@SiO2@n Fe3O4 nanoparticles.